Preschool science learning: The construction of representations and explanations about color, shadows, light and images - LETICIA GALLEGOS-CÁZARES; FERNANDO FLORES-CAMACHO; ELENA CALDERÓN-CANALES (Metaichmio Publications, 2009)
The present work shows the construction that preschool students can make about conceptions of color, light, formation of shadows and images in a plane mirror, with the application of a didactic proposal (EduCienPre) in which didactic sequences and materials are developed and which can be introduced to a classroom under normal conditions. The characteristics of the didactic proposal are described and preschoolers conceptual constructions are analyzed as a function of their explanations and representations. Analysis of children's actions in diverse physical situations offers deeper elements for understanding the construction of representations and scientific notions which could be reflected in a more adequate teaching of the sciences for small children.